Scope of Populus deltoides on Marginal Lands of Indo-gangetic Plains - Singh, Bajrang; Behl, H. M. (Indian Forester, 2001)
Experimental plantations of 3 clones of Populus deltoides (G3, G48 and D121) were evaluated in high density short rotation (4 yrs.) energy plantation (HDSREP) and conventional agroforestry plantations (AFP) of lO-yrs rotation on marginal lands. Clone D121, which was found better in HDSREP did not perform well in AFP trial. Whereas, clone G3 and G48, produced almost compatible biomass at 4 yrs and 8 yrs in these 2 sets of plantations. Proportions of stem biomass decreased with age. Nutrient accumulation was relatively high in G3 and D121 clones. Clone G48 has accumulated lowest N content in biomass and therefore appears to be better in nitrogen use efficiency. There are ample scope of Poplar cultivation on marginal lands of Gangetic plains to ensure some additional benefits either in HDSREP or in AFP over the slow growing indigenous trees. However, it is recommended in secondary plantation programmes to support and sustain the fast growth of this species. At first instance, abandoned marginal lands must be ameliorated substantially through the primary land use systems preferably with indigenous leguminous species. Therefore, cultivation of Poplar may be carried out to utilize such lands more efficiently with the appropriate soil and water management practices. However, yields equivalent to Tarai region of U.P. can not be expected due to limitations of environmental conditions.